Peningkatan Kapasitas Sistem Manajemen Pembelajaran Daring Berbasis Moodle Menggunakan Node On-Premises dan Cloud di Sekolah Binekas - Septiawan, Reza Rendian; Nasution, Surya Michrandi; Ruriawan, Muhammad Faris (Institut Riset dan Publikasi Indonesia (IRPI), 2024)
Hybrid learning, as a popular learning method to be used at different academic level, has the advantage of being a flexible and independent learning method which can be adjusted to each student's learning pace. In supporting hybrid learning, infrastructure upgrade is a must so that the system can fulfil dynamic requirement. Currently, Binekas School has already implementing a learning management system (LMS) platform. However, the existing condition of the LMS at Binekas School is not optimal since the architecture used does not allow to be accessed from an external network and the usage capacity is still not able to meet the needs of all students simultaneously. The current problems with the Binekas School LMS can be overcome by upgrading the capabilities of existing server equipment, both hardware and software. In addition, to increase the accessibility and reliability of the LMS system, it is necessary to integrate a hybrid architecture into the LMS platform, namely by combining on-premise servers with cloud-based architecture. The LMS platform used is Moodle which is one of the most popular LMS platforms. This community service activity is already succeeded in helping Binekas School to improve the capabilities of the existing LMS. Apart from that, by using cloud architecture, makes the LMS platform from Binekas School easier to access since it does not require users to be connected with Binekas School’s internal network. The Binekas School LMS platform can now be said to be fully functional and can be used as a model for other schools.